Belém, History, Politics, Architecture and Photography - Pinheiro , Nuno (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
Belém is one of Lisbon better known areas, It has some of the better known and most iconic monuments; they are among the most photographed since the 1860’s. Jerónimos Monastery and Belém Tower are symbolic of the Golden Age of Portuguese Seaborne Empire. These monuments gained a great importance in 19th century Portugal, as they were the stage of 1880’s Camões tri centennial, one of the most important political and social happenings of late 19th century Portugal. Before that they were the subject of stereo images made by Portuguese and foreign photographers, mostly for stereo card sale. They saw here an example of exotism, given by Manuelino Style, strong in Portugal, around 1500, and it’s heavy decoration with sea, and nature motifs. We will try to intersect History, Ideology, Architecture and History, to understand how this place became so important, as one of the places of memory for Portugal. We will question photography as an ideological tool of the bourgeois desire of building a visual account for History.